2016
DOI: 10.1186/s12931-016-0474-9
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory viral infections and host responses; insights from genomics

Abstract: Respiratory viral infections are a leading cause of disease and mortality. The severity of these illnesses can vary markedly from mild or asymptomatic upper airway infections to severe wheezing, bronchiolitis or pneumonia. In this article, we review the viral sensing pathways and organizing principles that govern the innate immune response to infection. Then, we reconstruct the molecular networks that differentiate symptomatic from asymptomatic respiratory viral infections, and identify the underlying molecula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
97
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(97 citation statements)
references
References 130 publications
(150 reference statements)
0
97
0
Order By: Relevance
“…Like all other viruses, IAV replication relies on many proteins or enzymes from the virus itself and the host cell (2). It is important to understand the mechanism of virus-host cell interaction to identify new therapeutic targets and develop antiviral drugs (3).…”
Section: Introductionmentioning
confidence: 99%
“…Like all other viruses, IAV replication relies on many proteins or enzymes from the virus itself and the host cell (2). It is important to understand the mechanism of virus-host cell interaction to identify new therapeutic targets and develop antiviral drugs (3).…”
Section: Introductionmentioning
confidence: 99%
“…This study also showed that palivizumab prophylaxis was effective mainly in subjects without a family history of atopy or food allergies, suggesting that RSV infection may represent a risk factor for future respiratory morbidity, independent from a genetic predisposition to atopy . A close evaluation of the complex interactions between RSV and the host is a key step in uncovering factors that could explain the pathogenicity of RSV infections also in “not‐at‐risk” populations .…”
Section: Rsv Bronchiolitis and Recurrent Wheezingmentioning
confidence: 66%
“…RSV is a single‐stranded RNA virus of the Paramyxoviridae family whose genome includes 10 genes encoding 11 proteins: three transmembrane surface glycoproteins (the attachment G protein, the fusion F protein, and the small hydrophobic SH protein), three proteins associate with the genomic RNA to form the nucleocapsid (the large L polymerase subunit, the N protein, and the phospho P protein), two non‐structural proteins (the NS1 and NS2 proteins), two transcription and replication factors (M2‐1 and M2‐2), and one unglycosylated matrix M protein (Fig. ) . Proteins F and G are key factors for virus attachment, fusion, and RSV nucleocapsid release into the cytoplasm, whereas viral transcription and subsequent replication require the L, N, P, M‐1, and M‐2 proteins that, together with the genomic RNA, form the ribonucleoprotein (RNP) complex.…”
Section: Rsv Structure and Functionmentioning
confidence: 99%
See 2 more Smart Citations